PENGARUH MOTIVASI DAN SIKAP KEWIRAUSAHAAN ISLAM TERHADAP MINAT BERWIRAUSAHA - Azid, Raka Malik; Hikmah, Sofi Faiqotul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The purpose of this study is: to partially and simultaneously influence the influence of Islamic Entrepreneurship Motivation and Attitudes simultaneously on Entrepreneurial Interest in Members of HIPMI PT IAIDA Blokagung Banyuwangi. This type of research is explanatory research and uses quantitative methods. The data analysis technique used multiple regression data analysis techniques. The results of this study are that there is an influence between Islamic Motivation and Entrepreneurial Attitudes partially on Entrepreneurial Interest in Members of HIPMI PT IAIDA Blokagung Banyuwangi with a tcount of 2,376 and 3,934 greater than the ttable value of 2,034. And there is an influence between Islamic Motivation and Entrepreneurial Attitudes simultaneously or jointly on Entrepreneurial Interest in Members of HIPMI PT IAIDA Blokagung Banyuwangi with a Fcount value of 19.464 greater than Ftable of 3.30. it can be concluded that there is an influence between Motivation and Islamic Entrepreneurial Attitudes partially and simultaneously on the Entrepreneurial Interest in Members of HIPMI PT IAIDA Blokagung Banyuwangi.